Monitoring sustainable energy development: a cross-country comparison of selected EU members - Kettner-Marx, Claudia; Kletzan-Slamanig, Daniela; Köppl, Angela; Zielinska, Irina (Vienna, 2019)
"Two major international frameworks provide landmarks for future development paths: the UN Sustainable Development Goals (SDGs) and the Paris Climate Agreement. Monitoring the progress towards achieving the individual goals has to consider a multitude of synergies and trade-offs. In this paper we use composite indices to analyse climate and energy policy in Austria and other selected EU countries. The analysis delivers several results which are also supported by the assessment of climate and energy policies in the case study countries. In general, the improvements regarding energy efficiency, emissions and deployment of renewables have been moderate in the period under observation. This hints at the time needed for restructuring to take place. This underlines the importance of credible political commitment to climate targets, the implementation of ambitious instruments and the need for stability in the guiding frameworks in order to effectuate substantial changes. In addition, the description of the circumstances and policy frameworks in the selected countries shows, that each one is characterised by a very specific energy system (complemented by specific social structures) which determines the challenges that have to be overcome on the way to decarbonisation."